Research Paper: Impact of Air Seat Cushions and Ball Chairs on Classroom Behavior of Students with Autism Spectrum Disorder - Nader Matin Sadr; Hojjat Allah Haghgoo; Sayyed Ali Samadi; Mehdi Rassafiani; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective Children with Autism Spectrum Disorder (ASD) have a lot of sensory integration problems, which severly interfere with their learning process in the classroom; therefore, they confront with difficult problems in academic achievements. As a result, they need environmental modification to resolve sensory seeking behaviors and improve their educational success. Considering the effects of sensory stimulation and integration in children with ASD, this study aimed to examine the impacts of sitting on a ball, cushion, and or common chair on classroom behavior of 4 students with ASD. Because alternative seating like therapy balls and air cushions instead of regular chairs can exert various sensory stimuli on student’s sensory organs, this study aimed to examine the effects of three alternative classroom-seating devices; i.e. regular classroom chairs, therapy balls, and air cushions on students’ classroom behaviors. These behaviors include on-seat behavior, on-task behavior, and autistic behavior. Materials & Methods In this study, 4 male students with ASD in Tabasom Primary School, Mashhad, Iran were investigated in a single-subject study. Their classroom behaviors were recorded and monitored by video recording in an A-B-A-C single-subject design for 4 weeks. Their classroom behaviors were video recorded in 3 phases: Students sat on a normal chair in baseline phases (A), on a cushions in second phase (B), and on a therapy ball in third phase (C). The students’ behaviors (including sitting times; in-seat and on-task/ off-task behaviors) were observed and recorded every other day, a session per day, and 10 minutes each session (in total 12 sessions equal to 120 minutes). Sitting times and on-task/off-task behaviors were quantified by momentary time sampling and compared during different phases for important changes. Social validity was taken by the teacher at the end of the research as well. Additionally, the Gilliam Autism Rating Scale - Second Edition test was used to examine stereotyped movements, social and communication skills of the students before and after the research. Social and communication skills of the subjects were evaluated before and after the intervention using The Vineland Social Maturity Scale. Statistical software SPSS version 19 and Excel software were used to analyze the descriptive statistics and drawing diagrams, respectively. Results The findings of this research demonstrated increases in on-task and in-seat behaviors in 4 students when seated on air sit cushioned chairs and therapy balls when compared to seating on regular chairs. But, despite increase in on-task behaviors for all students, only two of the students showed improved in-seat behaviors when seated on therapy balls. An increase of 11.7% in on-task behaviors was observed during sitting on a therapy ball, when compared to regular chairs. Furthermore, a 25% increase was observed in on-task behavior of students when they were seated on air sit cushioned chairs in comparison with regular chairs. The in-seat behaviors were increased by 31.7% and 23.3% when sitting on the therapy ball and cushioned air chairs, respectively, when compared with regular chairs. Social validity findings indicated that the teacher preferred the use of the balls and air-cushioned chairs for her students. Conclusion In the present study, therapy balls and or cushioned chairs for ASD students facilitated in-seat and on-task behaviors and improved classroom performance. It seems that using these alternative seating chairs can satisfy the subjects’ needs to sensory stimuli, and therefore, decreases their sensory seeking behaviors which interferes with their academic achievements. While, using therapy ball chairs for these students may facilitate in-seat behavior and decrease autistic behavior in class, the student’s response to dynamic seating is different individually. Therefore, chair selection must be based on vestibular reaction of the students.